Ulnar variance related to biological and training characteristics, pain and handgrip strength in Portuguese skeletally immature male gymnasts - Amaral, L.; Claessens, A. L.; Ferreirinha, J.; Santos, P. (Journal of Sport and Health Science, 2015)
Purpose: This study was to investigate the association between ulnar variance (UV) and biological and training characteristics, handgrip, and wrist pain in a group of 23 Portuguese skeletally immature male gymnasts (aged 11.2 ± 2.5 years). Methods: Left and right UV was obtained using Hafner's procedure and skeletal age was determined by the Tanner-Whitehouse 3-method. A negative mean value for UV measures was observed (-2.4 to -3.6 mm) without significant differences with increasing age-category (p = 0.09 to p = 0.48). Significant low correlations were observed between some UV parameters and stature, fat percentage, years of training, and left handgrip strength. Results: Ten gymnasts reported wrist pain with gradual onset and UV values were very similar between painless and painful wrists. Conclusion: The findings of this study do not directly support the thesis that gymnastics training and biological variables or wrist pain are associated with UV.